{((X-y) sqrty = sqrtx / 2), ((x + y) sqrtx = 3sqrty)}?

{((X-y) sqrty = sqrtx / 2), ((x + y) sqrtx = 3sqrty)}?
Anonim

Cevap:

# ((X, y), (- sqrt2, -1 / sqrt2), (sqrt2,1 / sqrt2), (- (3sqrt3) / 4, -sqrt3 / 4), ((3sqrt3) / 4, SQRT3 / 4)) #

Açıklama:

# {(x-y = 1/2 m2 (x / y)), (x + y = 3 sqrt (y / x)):} #

yani

# {(x ^ 2-y ^ 2 = 3/2), ((x-y) / (x + y) = 1 / 6x / y):} #

İçin çözme # X, y # alırız

# ((X, y), (- sqrt2, -1 / sqrt2), (sqrt2,1 / sqrt2), (- (3sqrt3) / 4, -sqrt3 / 4), ((3sqrt3) / 4, SQRT3 / 4)) #